Diagnostic Performance of Magnetic Resonance Imaging for Detection of Acute Appendicitis in Pregnant Women; a Systematic Review and Meta-Analysis - Mohsen Motavaselian; Fateme Bayati; Reza Amani-Beni; Amirreza Khalaji; Sara Haghverdi; Zeynab Abdollahi; Arash Sarrafzadeh; Amir-masood Rafie Manzelat; Amir Rigi; Razman Arabzadeh Bahri; Zahra Nakhaee; Mahta Fadaei; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: The diagnosis of acute appendicitis (AA) in pregnant women is commonly challenging owing to the normal results of laboratory tests, organ displacement, and normal physiological inflammatory alterations. This meta-analysis aimed to investigate the accuracy of magnetic resonance imaging (MRI) in diagnosis of AA in pregnant women.